The effect of ischemic preconditioning on the cardiac autonomic nervous system after exercise: A systematic review and meta-analysis - Chuan qiu shui Wang; Kun Wang; Hengxu Liu; Shi qi Liu; Yi Yang; Jiong Luo (Quality in Sport)
Aims: The objective of this study is to comprehensively evaluate the influence of ischemic preconditioning intervention on the autonomic control nerves of athletes during the post-exercise period.